Measurement of Cigarette Consumption of Indonesian People as Approach to Measurement of Cash Waqf Potential - Iindra Suwandi (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This article aims to provide an alternative approach to measuring the waqf potential that is clearly measured, by paying attention to economic behavior guidelines from an Islamic perspective while being able to reveal some of the fundamental problems of the people, especially Muslims in Indonesia. In addition, also to be able to propose the development of the Islamic consumption model as a useful contribution to the development of the Islamic economic concept more broadly. This is a literature study and uses secondary data, using inductive thinking patterns with development goals. Research activities are carried out by digging deeper from knowledge about measuring the potential for prior cash waqf and searching for related data and then developing it. This study has obtained the measurement of cigarette consumption as tabdzirÂ behavior as an alternative approach to measuring the potential of waqf that is clearly measured and meets good measurement needs. An Islamic consumption model that at the same time can provide awareness of the problems of the Ummah has also been developed.